Sistem Infomasi Geografis (SIG) Untuk Penyewaan Truck Angkel Menggunakan Metode Extreme Programming - Irfan ikhwanda; Hartanti, Dian; Srisulistiowati, Dwi Budi (Journal of Informatic and Information Security, 2025)
A well-prepared abstract enables the reader to identify the basic content of a document quickly Information technology is currently growing rapidly in various fields, one of which is in the field of transportation. In Indonesia, especially in the city of Bekasi, transportation has become a daily necessity for entrepreneurs, home industries and traders are needed, looking for safe transportation and economical prices is one of the main choices for entrepreneurs, then how do we get transportation costs at low prices, that is by finding the shortest or fastest path to get to the destination by Utilizing Geographic Information Systems. The purpose of this research is to make it easy for company admins to order online ordered by clients, this is where this idea emerged. This research is calculated using one method. Hire Truck rental rental, to be more efficient and accurate. The results of this research can be implemented in the form of a website-based geographic information system